107k views
0 votes
If K is the midpoint of HJ, HK= x + 6, and HJ = 4x - 6, then KJ equals

1 Answer

4 votes

Consider the figure,

We have,


\begin{gathered} HK=x+6 \\ \text{HJ}=4x-6 \end{gathered}

As we can understand from the figure that,

HJ=HK+KJ and HK=KJ


\begin{gathered} HJ=HK+KJ \\ 4x-6=x+6+KJ \\ 4x-6-x-6=KJ \\ 3x-12=KJ \\ 3x-12=x+6 \\ x=9 \\ \therefore KJ=3*9-12=15 \end{gathered}

,

If K is the midpoint of HJ, HK= x + 6, and HJ = 4x - 6, then KJ equals-example-1
User Bhadra
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.